THE ANALYSIS OF TEXBOOK “PATHWAY TO ENGLISH” USED IN THE SECOND GRADE OF SENIOR HIGH SCHOOL BASED ON CURRICULUM 2013 - Regina Rahmi; Sri Wahyuni; Intan Rahmalia (English Education Department, 2019)
This research analyzes the contents of the textbook ‘Pathway to English “with curriculum 2013 in providing the materials and exercise for the learning students. The data only choose the part of all chapter or 7 chapters in the textbook. Thus, this research focuses on the feasibility of the materials and exercises presented with core competence and basic competence in curriculum 2013 and also how the feasibility of the textbook based on curriculum 2013 with using BNSP assessment. This research uses a descriptive qualitative approach and the researcher uses document analysis as the method of collecting data. The result of this research is almost all of the chapters are suitable with curriculum 2013. It assessed by using the feasibility of content based on BNSP assessment which some subcomponents. Firstly, the compatibility of material items with core competence has 96% with a very good category. Secondly is the accuracy of material that gets a very good category too with 90% of item percentage. Thirdly, the learning supporting sources has 91% with a very good category too. The textbook is appropriate with curriculum 2013 and very helpful in increasing the skills (speaking, listening, reading and writing) in teaching and learning English. In this case, the textbook scored more 90% with very good category and the content of it is appropriate with curriculum 2013. In the other side, there is some minors incompatibility based on BNSP assessment in this textbook, such as lack of structure and element of meaning and development diversity concept in developing students' knowledge.